Association of varicose veins with the risk of heart failure: A nationwide cohort study. - Dongyeop Kim; Moo-Seok Park; Ju-Young Park; Tae-Jin Song (PLoS ONE)
Background Research investigating the association between varicose veins (VV) and heart failure has been limited. Here, we examine this association within a nationwide longitudinal cohort, hypothesizing an increased risk of heart failure associated with the presence of VV. Methods Our study included 390,436 participants based on health screening results conducted from 2005 to 2010 in the South Korean health screening cohort database. Presence of VV was defined as having at least two claims based on International Classification of Diseases, Tenth Revision (ICD-10) codes I830-832, I839, or I868. Propensity score matching (PSM) at a ratio of 1:5 was employed to categorize the participants into two groups based on the presence of VV. The primary outcome, heart failure incidence, was defined as two or more claims with ICD-10 code I50 during follow-up. Results Among the participants, presence of VV was noted in 5,008 (1.28%) individuals. Over a median follow-up period of 13.33 years (interquartile range 10.4-16.26), 55,023 cases of heart failure (14.0%) occurred. In the multivariable analysis, the group with VV consistently showed an increased incidence risk of heart failure compared to the group without VV, both before (hazard ratios [HR], 1.174; 95% confidence interval [CI], 1.089-1.265) and after PSM (HR, 1.171; 95% CI, 1.070-1.283). Landmark analysis also found a consistent relationship between the presence of VV and the incidence risk of heart failure before (HR, 1.190; 95% CI, 1.103-1.285) and after PSM (HR, 1.144; 95% CI, 1.044-1.254). Conclusions This study revealed a significant increase in the risk of heart failure among patients with VV in the general population of South Korea. Given that the presence of VV is likely associated with an increased risk of heart failure in the general population, the potential for future heart failure should be taken into consideration when VV are present.